2021
DOI: 10.1016/j.tics.2020.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Regulation of Empathy

Abstract: Empathy is an integral part of socio-emotional well-being, yet recent research has highlighted some of its downsides. Here we examine literature that establishes when, how much, and what aspects of empathy promote specific outcomes. After reviewing a theoretical framework which characterizes empathy as a suite of separable components, we examine evidence showing how dissociations of these components affect important socio-emotional outcomes and describe emerging evidence suggesting that these components can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 132 publications
5
80
0
5
Order By: Relevance
“…This is in agreement with former studies on the relation of individual's experiences through lifespan development with their functional architecture for the cognitive control of emotion (Ochsner and Gross, 2005). Accordingly, up-regulation or downregulation of emotion by the top-down cognitive control directs one's empathic response toward others as has been suggested in early and recent accounts on empathy (Decety and Lamm, 2006;Weisz and Cikara, 2021). Future studies should further elucidate this interesting, plausibly topdown driven, pattern by conducting connectivity analyses that would explore information trafficking across networks, and in-depth phenomenological interviews that would add the phenomenological dimension of this cognitive control phenomenon.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in agreement with former studies on the relation of individual's experiences through lifespan development with their functional architecture for the cognitive control of emotion (Ochsner and Gross, 2005). Accordingly, up-regulation or downregulation of emotion by the top-down cognitive control directs one's empathic response toward others as has been suggested in early and recent accounts on empathy (Decety and Lamm, 2006;Weisz and Cikara, 2021). Future studies should further elucidate this interesting, plausibly topdown driven, pattern by conducting connectivity analyses that would explore information trafficking across networks, and in-depth phenomenological interviews that would add the phenomenological dimension of this cognitive control phenomenon.…”
Section: Discussionsupporting
confidence: 91%
“…This finding indicated that the dichotomous affective-cognitive view does not straightforwardly accommodate human lived experiences and empathic encounters, and rather supports the Graded Empathy framework ( Levy and Bader, 2020 ). The results suggest that individuals with greater late alpha-beta enhancement have lower sensitivity to vicarious pain, whereas people with high sensitivity to vicarious pain have less inhibitory control in their brain ( Weisz and Cikara, 2021 ), thereby plausibly enabling them to empathize with others’ pain. This is in agreement with former studies on the relation of individual’s experiences through lifespan development with their functional architecture for the cognitive control of emotion ( Ochsner and Gross, 2005 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Empathy has been considered as a strong predictor of prosocial behaviors ( Roberts and Strayer, 1996 ). Empathy includes at least three related but distinct components – affective (feeling others’ emotions), cognitive (taking others’ perspective), and motivational (desiring to promote others’ well-being or alleviating their suffering) components ( Decety, 2015 ; Weisz and Cikara, in press ), based on shared and distinct neural systems ( Kogler et al, 2020 ). Empathy is crucial for well-being and indispensable in social life.…”
Section: Musical Training Boosts Empathy and Prosocial Behaviorsmentioning
confidence: 99%
“…Therefore, from a practical point of view, future studies need to compare and combine different interventions to achieve the optimal outcome of empathy development. Third, empathy is a multicomponent construct, and different situations might require different components ( Decety, 2015 ; Weisz and Cikara, in press ). It is possible that various music activities (e.g., singing, instrument playing, and group training) are applicable to different populations, and they may contribute unequally to a specific component of empathy.…”
Section: Implications and Future Directionsmentioning
confidence: 99%